Seeing through a glass darkly': casting light on imidazoline `I' sites - Eglen, Richard M.; Hudson, Alan L.; Kendall, David A.; Nutt, David J.; Morgan, Noel G.; Wilson, Vince G.; Dillon, Michael P. (Trends in pharmacological sciences (Regular ed.), 1998)
Although imidazoline sites have been the subject of research for several years, there is still controversy about their structure, diversity and physiology. The I 1 site is thought to exist principally as a binding site and is widely purported to play a role in controlling systemic blood pressure, although this is still unclear. The majority of I 2 sites are widely accepted as being allosteric sites on monoamine oxidase; however, even with selective ligands, their exact function remains to be determined. A putative I 3 site modulates insulin secretion and could represent the first functional site to be pharmacologically defined with selective agonists and antagonists. The structure and relevance of the proposed endogenous ligand `clonidine-displacing substance' remains elusive. A potential candidate for this substance is agmatine; however, although it is capable of displacing bound clonidine from imidazoline sites, it lacks the functionality ascribed to the clonidine-displacing substance. In this review, Richard M. Eglen and colleagues assess our knowledge of imidazoline sites in the light of recent data.